A distributed collaborative environment for distance learning applications - Mukerjee, Malay R. (Universiti Putra Malaysia, 1998)
Advances in computer use have created the concept of electronic documents that are much more flexible in content and shape than traditional paper ones. In particular, multimedia electronic documents can include features like text, graphics, images, animation, sound and video incorporated in the same document. Such features have numerous applications, one of the prominent. ones being that of interactive distance learning. Creation of such documents will benefit from the existence of a distributed collaborative environment that enables a group working together to share and edit such documents without space restrictions. Here we examine a proposal based on Java for implementing such an environment over the Internet.